How important is air quality in travel decision-making?. (September 2021) - Rodrigues, V.; Carneiro, M.J.; Eusébio, C.; Madaleno, M.; Robaina, M.; Gama, C.; Oliveira, K.; Relvas, H.; Lopes, M.; Monteiro, A.
Abstract: Air quality is a topic with growing interest within the tourism industry, especially for destinations with a high volume of tourism. Several implications on tourism demand are already recognised, such as influence on health and well-being, travel behaviour and trip satisfaction. However, there is a knowledge gap concerning its influence on tourism decision making. To overcome this gap this study intends to examine the relevance of destinations' air quality on tourism decision making before and during tourism trips. A qualitative study was carried out based on in-depth interviews with visitors from different cultural backgrounds and with different health conditions. A content analysis was undertaken to find the major references regarding the topic and to establish a comparative analysis. The results demonstrate a lack of concern regarding air quality in specific dimensions of travel planning. Nevertheless, when visitors are confronted with episodes of air pollution at the destination, they tend to adopt adaptive strategies to prevent negative effects. Differences were found between groups from different places of residence and between individuals with or without health problems. The paper ends with guidelines for those developing recreation and tourism activities concerning the relevance that should be assigned to air quality in the development of these activities. Management implications: Although AQ does not have a high influence in planning tourism trips, episodes of air pollution during the trip may greatly affect travel behaviour; Tourism managers should concentrate their efforts on the dissemination of information related to air quality, providing valuable insights to their potential visitors; Destinations with good air quality may have a competitive advantage, due to the growth of segments wishing to travel to unpolluted sites.